Saharo-Sindian endemic flora of Egypt: critical checklist, floristic analysis, habitats, and phytogeographic distribution - Abo Hatab, Asmaa S.; Al-Sodany, Yassin M.; Shaltout, Kamal H.; Haroun, Soliman A.; El-Khalafy, Mohamed M. (Phytotaxa, 2024)
The Saharo-Sindian region is characterized by savannas, semi-deserts, and hot deserts. This floristic region includes Morocco, Mauretania, Algeria, Libya, Egypt, Palestine, Kuwait, Saudi Arabia, Qatar, Bahrain, United Arab Emirates, Oman, Yemen, South of Jordan, Syria, Iraq, Afghanistan, Pakistan, in addition to the Sind region. The Sudano-Zambezian region, part of the Paleotropical Kingdom, and the Mediterranean and Irano-Turanian regions, included in the Holarctic Kingdom, share a significant portion of their flora with the studied region. This study initiates the examination of the Saharo-Sindian endemic plants occurring in Egypt. Its objectives include assessing the list of endemic plants within this floristic region, and studying various aspects such as: life forms, habitats, rarity forms, flowering times, dispersal types, and phytogeographical distribution. Twenty field trips were conducted from spring 2020 to September 2023, investigating different regions in Egypt. In addition, all the previous studies performed in the investigated area, scientific literature, and specimens from the region housed in different herbaria have been taken into consideration. The inventory of plants that are endemic to the Saharo-Sindian floristic region in Egypt comprises 126 plant taxa (109 species, 17 subspecies) distributed across 87 genera and 37 families. These endemics are found in 11 habitat types, with the most abundant occurrences observed in inland rocky areas (82 taxa) and temperate shrublands (57 taxa). Moreover, South Sinai stands out as the richest region for Saharo-Sindian endemics, hosting a remarkable 83 taxa, which constitute 65.9% of the total endemics. Among these, the chamaephytes group leads with 56 taxa, followed by the therophytes with 32 taxa. Pogonochores (45 taxa) are the most represented dispersal type. This study holds significant importance in evaluating a critical checklist of plants endemic to the Saharo-Sindian region in Egypt, contributing to our understanding of species diversity in regions facing severe anthropogenic disturbance. This list provides a foundational reference for future monitoring programs.